Water-based binder as well as preparation method and application thereof
By preparing an aqueous binder containing high content of unsaturated nitrile monomers, the problem of high impedance of lithium-ion batteries caused by existing PAA binders is solved, and the effect of reducing the internal resistance of the electrode sheet and improving the electrochemical performance of the battery is achieved.
Patent Information
- Application Number
- CN202411600561.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing solution-type PAA adhesives cause the lithium-ion battery to have a high impedance, affecting the battery's charge and discharge performance, cycle performance and temperature characteristics.
Using a water-based binder preparation method, the content of unsaturated nitrile monomer is controlled by preparing a protective glue solution and adding unsaturated carboxylic acid monomer, unsaturated nitrile monomer and acrylamide monomer to conduct polymerization reaction. At 65-75% by weight, a water dispersed binder with a hydrophilic structure is formed.
When applied to the negative electrode sheet, this water-based binder can maintain a good bonding effect, and at the same time retain a lithium ion transmission channel between the negative electrode active substance and the conductive agent, effectively reducing the internal resistance of the electrode sheet and improving the electrochemical performance of the battery .
Smart Images

Figure BDA0005128192470000161 
Figure BDA0005128192470000181 
Figure BDA0005128192470000182
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of binder material preparation, and in particular relates to a water-based binder and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used in energy storage, electric vehicles and consumer electronics due to their high energy density, long cycle life and low self-discharge rate. Lithium-ion batteries are mainly composed of positive electrodes, negative electrodes, electrolytes, diaphragms, and various auxiliary materials (conductive agents, binders). Among them, binders are crucial in lithium batteries. They can firmly adhere the electrode active material, conductive agent, and dispersant to the current collector to form a complete pole piece. At the same time, the binder effectively limits the volume expansion and shedding of the active material during the charge and discharge process, and can also reduce the interface impedance between the current collector and the electrode material.
[0003] According to the different dispersion media, lithium-ion battery binders can be divided into two categories: oily and water-based binders. Among them, the positive electrode mostly uses oily binder PVDF, but a large amount of N-methylpyrrolidone (NMP) needs to be added during its use, which is toxic and harmful to the environment. The negative electrode is mostly a more environmentally friendly water-based binder, such as polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC), styrene-butadiene latex (SBR), polyacrylic acid (PAA), and polyacrylonitrile (PAN). Among them, SBR is the most widely used negative electrode binder. Because it does not have the ability to suspend and disperse, it is usually used with a thickener CMC to improve the dispersibility of the slurry. However, the addition of CMC will bring new problems. Adding too much will increase the impedance of the battery; adding too little will cause problems such as low peeling force and high swelling.
[0004] Polyacrylic acid binder (PAA) is an emerging mainstream negative electrode binder, which usually contains a large number of carboxyl groups. On the one hand, it can form hydrogen bonds between the negative electrode active material and the current collector to exhibit excellent bonding performance; on the other hand, it can form intramolecular hydrogen bonds to exhibit strong cohesive force, and combined with its oleophobic structure, it will not be easily swollen by the electrolyte.
[0005] Although the solution-type PAA binder provided by the prior art has good resistance to electrolyte swelling and bonding performance, PAA usually has a dense coating on the active material and the conductive agent, and the polymer itself does not have the ability to conduct electricity, resulting in a high impedance of the lithium-ion battery, which has an adverse effect on the battery's charge and discharge performance, cycle performance and temperature characteristics. Summary of the invention
[0006] Therefore, the technical problem to be solved by the present invention is to overcome the defects of the solution-type PAA binder in the prior art that causes high battery impedance, affects the charge and discharge performance, cycle performance and temperature characteristics of the battery, thereby providing a water-based binder and its preparation method and application.
[0007] To this end, the present invention provides the following technical solutions.
[0008] The present invention provides a method for preparing a water-based binder, comprising the following steps:
[0009] (1) preparing a protective glue solution; adding a first polymerizable monomer and an initiator to the protective glue solution to carry out a polymerization reaction; the first polymerizable monomer comprises an unsaturated carboxylic acid monomer, an unsaturated nitrile monomer, and an acrylamide monomer; and the content of the unsaturated nitrile monomer in the first polymerizable monomer is not less than 15 wt %;
[0010] (2) adding a second polymerizable monomer and an initiator to the product of step (1) to carry out a polymerization reaction; the second polymerizable monomer comprises an unsaturated carboxylic acid monomer, an unsaturated nitrile monomer, an acrylamide monomer and a post-crosslinking monomer;
[0011] Based on the total weight of the first polymerized monomer and the second polymerized monomer, the total content of the unsaturated nitrile monomer in the first polymerized monomer and the second polymerized monomer is 65-75 wt %.
[0012] The first polymerized monomer accounts for 10-25 wt % of the total weight of the first polymerized monomer and the second polymerized monomer.
[0013] Furthermore, the preparation method satisfies at least one of (1)-(2):
[0014] (1) The mass of the unsaturated carboxylic acid monomer in the first polymerized monomer is not higher than 60 wt % of the total mass of the unsaturated carboxylic acid monomer in the first polymerized monomer and the second polymerized monomer;
[0015] (2) The total content of the unsaturated carboxylic acid monomer and the acrylamide monomer in the first polymerizable monomer is less than 85 wt %.
[0016] Furthermore, based on the total mass of the first polymerized monomer and the second polymerized monomer, the total content of the unsaturated carboxylic acid monomer is 15-30wt%, and / or the total content of the acrylamide monomer is 1-15wt%, and / or the content of the post-crosslinking monomer is not higher than 5wt%.
[0017] Furthermore, the preparation method satisfies at least one of (1) to (6):
[0018] (1) The unsaturated carboxylic acid monomer is at least one of acrylic acid, methacrylic acid, maleic acid and itaconic acid;
[0019] (2) the unsaturated carboxylic acid monomer is at least one of acrylic acid and methacrylic acid;
[0020] (3) The unsaturated nitrile monomer is at least one of acrylonitrile, α-haloacrylonitrile, and α-alkylacrylonitrile;
[0021] (4) The unsaturated nitrile monomer is acrylonitrile;
[0022] (5) The post-crosslinking monomer is a compound containing an acetoacetyl group;
[0023] (6) The post-crosslinking monomer is at least one of allyl acetoacetate and acetoacetoxyethyl methacrylate.
[0024] Furthermore, the preparation method satisfies at least one of (1)-(2):
[0025] (1) The protective colloid is at least one of polyvinyl alcohol, polyvinyl pyrrolidone and sodium carboxymethyl cellulose;
[0026] (2) The amount of the protective glue added is not higher than 1 wt % of the total weight of the first polymerized monomer and the second polymerized monomer.
[0027] Furthermore, the preparation method satisfies at least one of (1)-(2):
[0028] (1) The polymerization reaction temperature in step (1) is 30-90° C. and the reaction time is no more than 2 hours;
[0029] (2) The polymerization reaction temperature in step (2) is 30-90°C and the reaction time is 1.5-5h.
[0030] The present invention also provides a water-based adhesive prepared by the preparation method.
[0031] Furthermore, the aqueous binder satisfies at least one of (1)-(2):
[0032] (1) The solid content of the aqueous binder is 5-20%;
[0033] (2) The viscosity of the aqueous binder is 5000-50000 mPa·S.
[0034] The present invention also provides an aqueous binder prepared by the preparation method or use of the aqueous binder as a binder for negative electrode active materials.
[0035] The technical solution of the present invention has the following advantages:
[0036] 1. The preparation method of the aqueous binder provided by the present invention comprises: (1) preparing a protective glue solution; adding a first polymerizable monomer and an initiator to the protective glue solution, and carrying out a polymerization reaction; the first polymerizable monomer comprises an unsaturated carboxylic acid monomer, an unsaturated nitrile monomer, and an acrylamide monomer; the content of the unsaturated nitrile monomer in the first polymerizable monomer is not less than 15wt%; (2) adding a second polymerizable monomer and an initiator to the product of step (1), and carrying out a polymerization reaction; the second polymerizable monomer comprises an unsaturated carboxylic acid monomer, an unsaturated nitrile monomer, an acrylamide monomer, and a post-crosslinking monomer; based on the total mass of the first polymerizable monomer and the second polymerizable monomer, the total content of the unsaturated nitrile monomer in the first polymerizable monomer and the second polymerizable monomer is 65-75wt%. When the aqueous binder prepared by the preparation method is applied to a negative electrode plate, it has a good bonding effect and at the same time leaves sufficient lithium ion transmission channels between the negative electrode active material and the conductive agent, effectively reducing the internal resistance of the plate and improving the electrochemical performance of the battery.
[0037] 2. The aqueous adhesive provided by the present invention uses water as a dispersion medium, and does not require the use of additional organic solvents during the synthesis and subsequent electrode processing processes, and is an environmentally friendly adhesive. DETAILED DESCRIPTION
[0038] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0039] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0040] Existing solution-type polyacrylic acid binders have good resistance to electrolyte swelling and bonding performance, but PAA-type binders usually coat active materials and conductive agents more densely, and the polymer itself does not have conductivity, resulting in high impedance of lithium-ion batteries, which has an adverse effect on the battery's charge and discharge performance, cycle performance and temperature characteristics. In order to solve the problems existing in the prior art, the present invention provides the following technical solutions.
[0041] In a first aspect, the present invention provides a method for preparing a water-based binder, comprising:
[0042] (1) preparing a protective gel solution; adding the protective gel solution to a reaction kettle, introducing an inert gas, stirring, heating, adding a first polymerization monomer and an initiator, and performing a polymerization reaction; after the reaction is completed, adding a neutralizer to adjust the pH;
[0043] The first polymerizable monomers include unsaturated carboxylic acid monomers, unsaturated nitrile monomers and acrylamide monomers; the content of the unsaturated nitrile monomers in the first polymerizable monomers is not less than 15 wt %;
[0044] (2) adding a second polymerization monomer and an initiator to the product of step (1) to initiate a polymerization reaction; after the reaction is completed, adding and eliminating an initiator aqueous solution and keeping the temperature; after the insulation is completed, adjusting the temperature in the kettle to 60-90° C., adding a neutralizer to adjust the pH, and obtaining a dispersed water-based binder.
[0045] The second polymerizable monomers include unsaturated carboxylic acid monomers, unsaturated nitrile monomers, acrylamide monomers and post-crosslinking monomers; based on the total mass of the first polymerizable monomers and the second polymerizable monomers, the content of the unsaturated nitrile monomers in the first polymerizable monomers and the second polymerizable monomers is 65-75wt%.
[0046] When the binder prepared by the present invention is applied to the negative electrode plate, it has a good bonding effect and retains sufficient lithium ion channels between the negative electrode active material and the conductive agent, effectively reducing the internal resistance of the plate and improving the electrochemical performance of the battery. In step (1) of the present invention, the proportion of polymerized monomers is precisely regulated to ensure that the product of step (1) has good water solubility and a certain hydrophobicity, and acts as a solubilizing agent, so that the intermediate product obtained in this step has a good solubilizing effect on the polymerized monomers and polymers in step (2) (polymers include the polymerized intermediate products and the final polymerized products of step (2)). In step (1), the content of the unsaturated nitrile monomer is regulated to be not less than 15wt%, so that the product of this step has a certain hydrophobicity. The binder prepared by the present invention has a hydrophilic-hydrophobic structure and is a water-dispersible binder. When used as a binder for negative electrode active materials, it exhibits low internal resistance performance.
[0047] Further, the intermediate product obtained in step (1) provides a uniform polymerization environment for the polymerization monomer in step (2), does not participate in the polymerization reaction in step (2), plays a solubilizing agent, and can fully ensure the uniform copolymerization of each monomer in step (2); as the molecular weight of the polymerization product gradually increases, due to its relatively hydrophobic structure, it associates with each other, driving the intermediate product in step (1) to precipitate from water together, and forms an aqueous dispersion under stirring. Since the intermediate product in step (1) has a large number of carboxyl units, it has excellent stability in water by virtue of the ion repulsion effect after alkali neutralization, which provides the necessary conditions for the stable existence of the final microscopic form of the binder. The present invention regulates the total addition amount of the unsaturated nitrile monomer to be 65-75wt% of the total mass of the first polymerization monomer and the second polymerization monomer, and controls the content of the unsaturated nitrile monomer in the first polymerization monomer in step (1) to be not less than 15wt%, so that the polymer can be soluble in water while also having a certain hydrophobic structure; in step (2), a large amount of unsaturated nitrile monomers are added, and the polymer component with a unique hydrophilic and hydrophobic structure is obtained in combination with the intermediate product in step (1), thereby further forming an aqueous dispersion.
[0048] The aqueous binder prepared by the present invention is a water-dispersible binder. When applied to the negative electrode, the water-dispersible binder and the active material are point-bonded, which is different from the surface bonding between the solution-type PAA binder and the active material in the prior art. Compared with the prior art, the water-dispersible binder of the present invention can provide a smoother conduction path for lithium ions between the active material and the conductive agent, and the internal resistance of the obtained pole piece is lower. The binder provided by the present invention has good affinity with the active material, has good suspension stability for the active material, and the configured slurry is not easy to settle.
[0049] In an optional embodiment, the first polymerized monomer accounts for 10-25wt% of the total weight of the first polymerized monomer and the second polymerized monomer. Optionally, the first polymerized monomer accounts for 13-20% of the total weight of the first polymerized monomer and the second polymerized monomer. The present invention controls the content of the first polymerized monomer to help the molecular weight of the intermediate product of step (1) be less than the molecular weight of the product of step (2), and the product of step (1) has no cross-linked structure. If the content of the first polymerized monomer is too much, it will affect the bonding performance of the adhesive.
[0050] In an optional embodiment, the amount of the unsaturated carboxylic acid monomer in the first polymerized monomer is not higher than 60wt% of the total weight of the unsaturated carboxylic acid monomers in the first polymerized monomer and the second polymerized monomer. If the content of the unsaturated carboxylic acid monomer in the second polymerized monomer is too low, the hydrophobicity of the product of step (2) will become stronger, and it will be easy to precipitate from the system, which is not conducive to stability.
[0051] In an optional embodiment, the total content of the unsaturated carboxylic acid monomer and the acrylamide monomer in the first polymerizable monomer is less than 85 wt %, which can further ensure the hydrophilicity and hydrophobicity of the product of step (1) and have a solubilizing effect on the polymerization process of step (2).
[0052] In an optional embodiment, based on the total mass of the first polymerized monomer and the second polymerized monomer, the total content of the unsaturated carboxylic acid monomer is 15-30wt%, and / or the total content of the acrylamide monomer is 1-15wt%, and / or the content of the post-crosslinking monomer is not higher than 5wt%.
[0053] In an optional embodiment, the unsaturated carboxylic acid monomer is at least one of acrylic acid, methacrylic acid, maleic acid and itaconic acid;
[0054] The unsaturated carboxylic acid monomer is at least one of acrylic acid and methacrylic acid;
[0055] In an optional embodiment, the unsaturated nitrile-based monomer is at least one of acrylonitrile, α-haloacrylonitrile, and α-alkylacrylonitrile; for example, methacrylonitrile, ethacrylonitrile, and the like.
[0056] The post-crosslinking monomer is a compound containing acetoacetyl. The post-crosslinking monomer has a high-temperature self-crosslinking structure, and chemical crosslinking occurs by means of the baking process of preparing the pole piece, giving the binder good bonding strength and resistance to electrolyte swelling. The diketone structure in the post-crosslinking monomer chelates with the metal, further enhancing the adhesion of the binder to the current collector.
[0057] In an optional embodiment, the protective colloid is at least one of polyvinyl alcohol, polyvinyl pyrrolidone and sodium carboxymethyl cellulose;
[0058] The amount of the protective glue added is not higher than 1 wt % of the total weight of the first polymerized monomer and the second polymerized monomer.
[0059] In an optional embodiment, the polymerization reaction temperature in step (1) is 30-90°C, and the time is not more than 2 hours; optionally, the polymerization reaction temperature in step (1) is 35-85°C, and the time is 0.5-1.5 hours. As an example, the polymerization reaction temperature is 30°C, 40°C, 50°C, 60°C, 70°C, 90°C, or any two numerical ranges.
[0060] In an optional embodiment, the polymerization reaction temperature in step (2) is 30-90°C, and the time is 1.5-5h; optionally, the polymerization reaction temperature in step (2) is 35-85°C, and the time is 2-4h. As an example, the polymerization reaction temperature is 30°C, 40°C, 50°C, 60°C, 70°C, 90°C, or any two numerical ranges.
[0061] In an optional embodiment, the time of keeping warm after adding the post-elimination initiator aqueous solution in step (2) is 1-3 hours, preferably 1.5-2 hours. The post-elimination initiator of the present invention can further improve the conversion rate of the polymerization monomer and reduce the residual monomer in the polymer.
[0062] In an optional embodiment, in step (1) and step (2), the neutralizing agent is selected from at least one of Na2CO3, K2CO3, Li2CO3, NaOH, KOH, and LiOH aqueous solutions.
[0063] In an optional embodiment, the initiator adopts the type of initiator known in the art, and the initiator is a thermal initiator or a redox system initiator; the oxidant in the redox system initiator is at least one of ammonium persulfate, potassium persulfate, sodium persulfate, tert-butyl hydroperoxide and hydrogen peroxide, preferably ammonium persulfate and potassium persulfate; the reducing agent is at least one of isoascorbic acid, sodium pyrosulfite, sodium bisulfite and sodium hydrosulfite, preferably isoascorbic acid and sodium pyrosulfite. The thermal initiator can be ammonium persulfate APS, etc., and the amount of the thermal initiator added adopts the amount known in the art.
[0064] In an optional embodiment, the total amount of oxidant in step (1) and step (2) is 0.11wt%, preferably 0.20.8wt% of the total amount of the first polymerized monomer and the second polymerized monomer; the total amount of reducing agent in step (1) and step (2) is 0.11wt%, preferably 0.20.8wt% of the total amount of the first polymerized monomer and the second polymerized monomer.
[0065] In step (1), the amount of the oxidant is 1-25wt% of the total amount of the oxidant in step (1) and step (2), preferably 5-20wt%; the amount of the reducing agent is 1-25wt% of the total amount of the reducing agent in step (1) and step (2), preferably 5-20wt%. In step (2), the amount of the oxidant is 75-99wt% of the total amount of the oxidant in step (1) and step (2), preferably 80-95wt%; the amount of the reducing agent is 75-99wt% of the total amount of the reducing agent in step (1) and step (2), preferably 80-95wt%.
[0066] Secondly, the present invention provides a water-based binder in which the polymer molecular chains tend to be clustered rather than stretched in water. Compared with the solution-type PAA binder, it still has a suitable viscosity at a higher solid content, which facilitates the subsequent slurry configuration and electrode coating process.
[0067] The aqueous binder satisfies at least one of (1)-(2):
[0068] (1) The solid content of the aqueous binder is 5-20%;
[0069] (2) The viscosity of the aqueous binder is 5000-50000 mPa·S.
[0070] In a third aspect, the present invention provides the use of an aqueous binder as a binder for negative electrode active materials, wherein the negative electrode active materials are common materials in the art, such as artificial graphite, natural graphite, hard carbon, silicon carbon, and the like.
[0071] The present application is further described in detail below in conjunction with specific examples, which should not be construed as limiting the scope of protection claimed in the present application. Unless otherwise specified, the chemical reagents used in each example and comparative example can be purchased from the market, and the purity is analytically pure, and the main raw materials are as follows:
[0072] Acrylic acid (AA), manufacturer: Wanhua Chemical; methacrylic acid (MAA), manufacturer: Wanhua Chemical; acrylamide (AM), manufacturer: Wanhua Chemical; acrylonitrile (AN), manufacturer: Wanhua Chemical; allyl acetoacetate (AAA), manufacturer: Myrel; ammonium persulfate (APS), manufacturer: Jinan Jinhao Chemical Co., Ltd.; sodium persulfate (SPS), manufacturer: Jinan Jinhao Chemical Co., Ltd.; sodium metabisulfite (Na2S2O5), manufacturer: Wanhua Chemical; sodium carboxymethyl cellulose (CMC), manufacturer: Sinopec Sichuan Wei Co., Ltd.; polyvinyl alcohol (PVA), manufacturer: Sinopharm Chemical; polyvinyl pyrrolidone (PVP), manufacturer: Sinopharm Chemical; sodium hydroxide (NaOH), manufacturer: Inotech; conductive carbon black (Super-P), manufacturer: Yirui Shi Group; graphite (G), manufacturer: Shanshan Co., Ltd.
[0073] Example 1
[0074] This embodiment provides a method for preparing a water-based binder, comprising the following steps:
[0075] (1) 60g AA, 5g AM and 25g AN are mixed to obtain a first polymerization monomer, which is set aside. 80g AA, 20g AM, 300g AN and 10g AAA are mixed to obtain a second polymerization monomer, which is set aside. 0.5g SPS (sodium persulfate) is dissolved in 30g deionized water to obtain an oxidant solution, 0.25g Na2S2O5 is dissolved in 30g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a first initiator, which is set aside. 2.5g SPS is dissolved in 50g deionized water to obtain an oxidant solution, 1.25g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a second initiator, which is set aside. 3g SPS is dissolved in 50g deionized water to obtain an oxidant, and 1.5g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent, which is used as a post-elimination initiator, which is set aside.
[0076] 3g CMC and 2000g deionized water were added to the reactor, stirred under nitrogen atmosphere and set to 45°C for heating, stirred and dissolved to obtain a protective glue solution. The first polymerization monomer was added to the reactor, followed by dropwise addition of the first initiator for 15 minutes. After the addition was completed, the temperature was kept at 45 minutes, and a sodium hydroxide aqueous solution (15wt%) was added to adjust the pH to 7-8.
[0077] (2) Keeping the set temperature at 45°C unchanged, the second polymerization monomer and the second initiator are added to the reactor simultaneously, the addition time is 3 hours, and the temperature is kept for 1 hour after the addition is completed. Then, the initiator is eliminated after the addition, the addition time is 1 hour, and the temperature is kept for 1 hour after the addition is completed. Then, the temperature is raised to 70°C, and after the temperature stabilizes, sodium hydroxide aqueous solution (15wt%) is added to adjust the pH to 7-8, and after the pH stabilizes, the temperature is kept for 2 hours, and the material is filtered to obtain the target binder.
[0078] Example 2
[0079] The present embodiment provides a method for preparing a water-based adhesive, which is basically the same as the embodiment 1, except that: ① the heating temperature of the reactor is set at 80°C instead of 45°C; ② the first initiator, the second initiator and the post-elimination initiator are different; in the present embodiment, the first initiator uses APS instead of SPS and Na2S2O5, and the mass of APS is the total amount of SPS and Na2S2O5; the second initiator uses APS instead of SPS and Na2S2O5, and the mass of APS is the total amount of SPS and Na2S2O5; the post-elimination initiator uses APS instead of SPS and Na2S2O5, and the mass of APS is the total amount of SPS and Na2S2O5.
[0080] Example 3
[0081] This embodiment provides a method for preparing a water-based binder, which is basically the same as that of Embodiment 1, except that polyvinyl alcohol or the like is used instead of CMC.
[0082] Example 4
[0083] This embodiment provides a method for preparing a water-based binder, comprising the following steps:
[0084] (1) 80g AA, 15g AM and 20g AN are mixed to obtain a first polymerization monomer, which is set aside. 60g AA, 15g AM, 305g AN and 5g AAA are mixed to obtain a second polymerization monomer, which is set aside. 0.6g SPS is dissolved in 30g deionized water to obtain an oxidant solution, 0.3g Na2S2O5 is dissolved in 30g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a first initiator, which is set aside. 2.4g SPS is dissolved in 50g deionized water to obtain an oxidant solution, 1.2g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a second initiator, which is set aside. 3g SPS is dissolved in 50g deionized water to obtain an oxidant solution, and 1.5g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent solution, which is used as a post-elimination initiator, which is set aside.
[0085] 3g CMC and 2000g deionized water were added to the reactor, stirred under nitrogen atmosphere and set to 45°C for heating, stirred and dissolved to obtain a protective glue solution. The first polymerization monomer was added to the reactor, followed by dropwise addition of the first initiator for 15 minutes. After the addition was completed, the temperature was kept at 45 minutes, and a sodium hydroxide aqueous solution (15wt%) was added to adjust the pH to 7-8.
[0086] (2) Keeping the set temperature at 45°C unchanged, the second polymerization monomer and the second initiator are added to the reactor simultaneously, the addition time is 3 hours, and the temperature is kept for 1 hour after the addition is completed. Then, the initiator is eliminated after the addition, the addition time is 1 hour, and the temperature is kept for 1 hour after the addition is completed. Then, the temperature is raised to 70°C, and after the temperature stabilizes, sodium hydroxide aqueous solution (15wt%) is added to adjust the pH to 7-8, and after the pH stabilizes, the temperature is kept for 2 hours, and the material is filtered to obtain the target binder.
[0087] Example 5
[0088] This embodiment provides a method for preparing a water-based binder, comprising the following steps:
[0089] (1) 30g AA, 5g AM and 25g AN are mixed to obtain a first polymerization monomer, which is set aside. 90g AA, 5g AM, 330g AN and 15g AAA are mixed to obtain a second polymerization monomer, which is set aside. 0.3g SPS is dissolved in 30g deionized water to obtain an oxidant solution, 0.15g Na2S2O5 is dissolved in 30g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a first initiator, which is set aside. 2.7g SPS is dissolved in 50g deionized water to obtain an oxidant solution, 1.35g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a second initiator, which is set aside. 3g SPS is dissolved in 50g deionized water to obtain an oxidant solution, and 1.5g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent solution, which is used as a post-elimination initiator, which is set aside.
[0090] 3g CMC and 2000g deionized water were added to the reactor, stirred and heated at 45°C under nitrogen atmosphere, stirred and dissolved to obtain a protective glue solution. The first polymerization monomer was added to the reactor, and then the first initiator was added dropwise for 15 minutes. After the addition was completed, the temperature was kept for 45 minutes, and a sodium hydroxide aqueous solution (15wt%) was added to adjust the pH to 7-8.
[0091] (2) Keeping the set temperature at 45°C unchanged, the second polymerization monomer and the second initiator are added to the reactor simultaneously, the addition time is 3 hours, and the temperature is kept for 1 hour after the addition is completed. Then, the initiator is eliminated after the addition, the addition time is 1 hour, and the temperature is kept for 1 hour after the addition is completed. Then, the temperature is raised to 70°C, and after the temperature stabilizes, sodium hydroxide aqueous solution (15wt%) is added to adjust the pH to 7-8, and after the pH stabilizes, the temperature is kept for 2 hours, and the material is filtered to obtain the target binder.
[0092] Example 6
[0093] This embodiment provides a method for preparing a water-based binder, comprising the following steps:
[0094] (1) 60g AA, 5g AM and 25g AN are mixed to obtain a first polymerization monomer, which is set aside. 80g AA, 20g AM, 305g AN and 5g AAA are mixed to obtain a second polymerization monomer, which is set aside. 0.5g SPS is dissolved in 30g deionized water to obtain an oxidant solution, 0.25g Na2S2O5 is dissolved in 30g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a first initiator, which is set aside. 2.5g SPS is dissolved in 50g deionized water to obtain an oxidant solution, 1.25g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a second initiator, which is set aside. 3g SPS is dissolved in 50g deionized water to obtain an oxidant solution, and 1.5g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent solution, which is used as a post-elimination initiator, which is set aside.
[0095] 3g CMC and 2000g deionized water were added to the reactor, stirred under nitrogen atmosphere and set the heating temperature to 30°C, stirred and dissolved to obtain a protective glue solution. The first polymerization monomer was added to the reactor, and then the first initiator was added dropwise for 15min. After the addition was completed, the temperature was kept for 45min, and the solution (wt%) was added to adjust the pH to 7-8.
[0096] (2) Keeping the set temperature at 45°C unchanged, the second polymerization monomer and the second initiator are added to the reactor simultaneously, the addition time is 1.5 hours, and the temperature is kept for 1 hour after the addition is completed. Then, the initiator is eliminated after the addition, the addition time is 30 minutes, and the temperature is kept for 1 hour after the addition is completed. Then, the temperature is raised to 70°C, and after the temperature stabilizes, sodium carbonate aqueous solution (15wt%) is added to adjust the pH to 7-8, and after the pH stabilizes, the temperature is kept for 2 hours, and the material is filtered to obtain the target binder.
[0097] Comparative Example 1
[0098] This comparative example provides a method for preparing a water-based binder, comprising the following steps:
[0099] (1) 140 g AA, 25 g AM, 325 g AN and 10 g AAA were mixed to obtain a polymerization monomer, which was set aside. 3.0 g SPS was dissolved in 80 g deionized water to obtain an oxidant solution, and 1.5 g Na2S2O5 was dissolved in 80 g deionized water to obtain a reducing agent solution, thereby obtaining a redox system initiator, which was used as an initiator and set aside. 3 g SPS was dissolved in 50 g deionized water to obtain an oxidant solution, and 1.5 g Na2S2O5 was dissolved in 50 g deionized water to obtain a reducing agent solution, which was used as a post-elimination initiator and set aside.
[0100] 3g CMC and 2000g deionized water were added to the reactor, stirring was started under nitrogen atmosphere, the heating temperature was set to 45°C, stirring and dissolving, and a protective glue solution was obtained. The polymerization monomer and initiator were simultaneously added dropwise to the reactor, the addition time was 3h, and the temperature was kept for 1h after the addition was completed. Then the initiator was eliminated after the addition, the addition time was 1h, and the temperature was kept for 1h after the addition was completed. This comparative example lacked the solubilization and protection of the macromolecular solubilizer during the reaction process, so the relatively hydrophobic polymerization product could not be stably and uniformly present in the water, and then precipitated from the water and condensed into blocks, the polymerization product precipitated in large quantities, the condensation was serious, and the neutralization step could not be carried out, and the binder was not obtained.
[0101] Comparative Example 2
[0102] This comparative example provides a method for preparing a water-based binder, comprising the following steps:
[0103] (1) 60g AA and 5g AM are mixed to obtain a first polymerization monomer, which is set aside. 80g AA, 20g AM, 325g AN and 10g AAA are mixed to obtain a second polymerization monomer, which is set aside. 0.5g SPS is dissolved in 30g deionized water to obtain an oxidant solution, and 0.25g Na2S2O5 is dissolved in 30g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a first initiator, which is set aside. 2.5g SPS is dissolved in 50g deionized water to obtain an oxidant solution, and 1.25g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a second initiator, which is set aside. 3g SPS is dissolved in 50g deionized water to obtain an oxidant solution, and 1.5g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent solution, which is used as a post-elimination initiator, which is set aside.
[0104] 3g CMC and 2000g deionized water were added into the reactor, stirred under nitrogen atmosphere and set the heating temperature to 45°C, stirred and dissolved to obtain a protective glue solution. The first polymerization monomer was added into the reactor, and then the first initiator was added dropwise for 15min. After the addition was completed, the temperature was kept for 45min, and a sodium hydroxide aqueous solution (15wt%) was added to adjust the pH to 7-8.
[0105] (2) The second polymerization monomer and the second initiator were simultaneously added dropwise to the reactor for 3 hours, and the mixture was kept warm for 1 hour after the addition. Then, the initiator was eliminated after the addition, and the addition time was 1 hour. After the addition was completed, the mixture was kept warm for 1 hour. In this comparative example, no acrylonitrile was added in step (1), and the solubilization effect of the intermediate product in step (1) was limited. The polymerization product in step (2) precipitated in large quantities and coagulated severely, so the neutralization step could not be performed, and no binder was obtained.
[0106] Comparative Example 3
[0107] This comparative example provides a method for preparing a water-based binder, which is basically the same as Example 1, except that the second polymerizable monomer does not contain the post-crosslinking monomer AAA.
[0108] Comparative Example 4
[0109] This comparative example provides a method for preparing a water-based binder, which is basically the same as Example 1, except that the crosslinking monomer in the second polymerizable monomer is divinylbenzene.
[0110] Comparative Example 5
[0111] This comparative example provides a method for preparing a water-based binder, which is basically the same as Example 1, except that the total amount of acrylonitrile used is 49% of the total amount of the first polymerizable monomer and the second polymerizable monomer. The first polymerizable monomer and the second polymerizable monomer have the following compositions, and the preparation method is the same as Example 1.
[0112] (1) 80g AA, 20g AM and 50g AN are mixed to obtain a first polymerization monomer, which is set aside. 120g AA, 30g AM, 200g AN and 10g AAA are mixed to obtain a second polymerization monomer, which is set aside. 0.8g SPS is dissolved in 30g deionized water to obtain an oxidant solution, 0.4g Na2S2O5 is dissolved in 30g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a first initiator, which is set aside. 2.2g SPS is dissolved in 50g deionized water to obtain an oxidant solution, 1.1g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent solution, and a redox system initiator is obtained as a second initiator, which is set aside. 3g SPS is dissolved in 50g deionized water to obtain an oxidant solution, and 1.5g Na2S2O5 is dissolved in 50g deionized water to obtain a reducing agent solution, which is used as a post-elimination initiator, which is set aside.
[0113] 3g CMC and 2000g deionized water were added to the reactor, stirred under nitrogen atmosphere and set to 45°C for heating, stirred and dissolved to obtain a protective glue solution. The first polymerization monomer was added to the reactor, followed by dropwise addition of the first initiator for 15 minutes. After the addition was completed, the temperature was kept at 45 minutes, and a sodium hydroxide aqueous solution (15wt%) was added to adjust the pH to 7-8.
[0114] (2) Keeping the set temperature at 45°C unchanged, the second polymerization monomer and the second initiator are added to the reactor simultaneously, the addition time is 3 hours, and the temperature is kept for 1 hour after the addition is completed. Then, the initiator is eliminated after the addition, the addition time is 1 hour, and the temperature is kept for 1 hour after the addition is completed. Then, the temperature is raised to 70°C, and after the temperature stabilizes, sodium hydroxide aqueous solution (15wt%) is added to adjust the pH to 7-8, and after the pH stabilizes, the temperature is kept for 2 hours, and the material is filtered to obtain the target binder.
[0115] Test Case
[0116] This test example provides the performance of the binder, with the commercially available SBR3001A / BCQ15-2CMC binder system as control group 1 and the commercially available Indile LA136D PAA binder as control group 2, as follows:
[0117] (I) Electrolyte swelling evaluation method: The adhesive is dried to form a film to test the swelling of the adhesive in the electrolyte. Specifically, the adhesive solution is dried in a 50°C oven to form a film, and a membrane with a mass of M1 is taken; the membrane is immersed in the electrolyte (the volume ratio of EC, EMC and DEC is 3:5:2) and placed in a 60°C oven for 48 hours, and the electrolyte on the surface of the membrane is wiped dry with filter paper, and the weight is recorded as M2. The electrolyte swelling degree is calculated using the following formula:
[0118]
[0119] (ii) Preparation of negative electrode for lithium-ion battery: Add 0.1 parts of CMC to 150 parts of deionized water at room temperature, stir at high speed for 20 minutes, then add 2 parts of conductive carbon black sp, 96 parts of negative electrode active material (graphite) and 1.9 parts of binder (from each embodiment, comparative example and control group), and filter through a 100-mesh filter to obtain negative electrode slurry. It should be noted that in the process of preparing the slurry, each chemical substance added needs to be stirred at high speed for 15 minutes to mix evenly, and then continue to add the next chemical substance. The filtered slurry is coated on a copper foil with a thickness of 10 μm, and the coating thickness of the slurry is 100 μm, then placed in 135°C for 25 minutes, naturally cooled to room temperature in the furnace, and rolled by a roller press to obtain an electrode sheet. The electrode sheet was evaluated for slurry dispersibility, peel strength and electrochemical performance.
[0120] Peel strength evaluation method: The instrument uses a Kejian tensile testing machine, specifically: cut the electrode pole piece prepared above into a pole piece with a length of 200mm and a width of 25mm along the rolling direction. Use 3M double-sided tape to stick the pole piece flatly on a smooth steel plate, then fix the stainless steel plate on the tensile machine, and reversely clamp the pole piece not attached to the tape on the tensile machine probe. The tensile machine base pulls the pole piece at a speed of 10cm / min, and the sensor measures the peeling force during the process. For each group of 5 parallel samples, the average value is the final peel strength, in N / m.
[0121] Binder slurry viscosity evaluation method: The instrument uses a Brookfield DV2T model tester, specifically: place the pre-temperatured (40°C) slurry (the above-mentioned negative electrode slurry) under the instrument, select the 64# rotor, 12rpm test conditions for testing, keep the rotor groove level with the liquid surface, start the test, read the viscosity reading after it stabilizes, test 3 times, and take the average value. The negative electrode slurry viscosity test method is the same as the binder slurry.
[0122] Evaluation method of slurry stability: Place the prepared negative electrode slurry at room temperature for 2 days, observe the stratification of the slurry, and test the solid content of the upper and lower layers of the slurry to determine the stability of the slurry. The upper and lower layers refer to the upper and lower surfaces of the slurry container, respectively.
[0123] (III) Electrochemical performance evaluation method: The positive electrode sheet is prepared using lithium iron phosphate as the positive electrode active material. The preparation method is the same as that of the negative electrode sheet. The negative electrode sheet and the positive electrode sheet made of a binder are assembled into an aluminum-plastic soft package battery, and then the electrochemical performance of the battery is tested.
[0124] DCR: Under normal temperature conditions, the battery cell is discharged to 2.75V at a constant current of 1C, left to stand, and then charged to 4.2V at a constant current of 1C, and a constant voltage of 4.2V; then the battery cell is discharged to 2.8V at a current rate of 1C, and the capacity is recorded. After 2-4 cycles, the last discharge capacity is used as the 100% capacity value of the battery cell for subsequent DCR tests. At the target temperature, the battery cell is charged to 4.2V at a current rate of 1C, and a constant voltage of 4.2V; then the battery cell is discharged to 50% SOC at a current rate of 1C, and left to stand. The battery cell is discharged at 3C for 30s, and then discharged to 2.75V at a current rate of 1C. The DCR value, that is, the DC resistance, is calculated using the Ohm's law formula, as follows:
[0125]
[0126] Capacity retention rate: Charge to 4.2V with a current of 1C rate and keep the voltage at 4.2V; then discharge the battery with a current of 1C rate, with a cut-off voltage of 2.75V, completing one cycle. Test the capacity retention rate after 1000 cycles.
[0127] Charging rate: Under normal temperature conditions, discharge the battery cell at a current rate of 1C to 2.5V and maintain a constant voltage of 2.5V; then discharge the battery cell at a current rate of 1C, with a cut-off voltage of 4.2V.
[0128] Discharge rate: Under normal temperature conditions, charge the battery cell to 4.75V at a current rate of 1C and maintain a constant voltage of 4.75V; then discharge the battery cell at a current rate of 1C, with a cut-off voltage of 2.5V.
[0129] Table 1 Physical properties test results
[0130]
[0131]
[0132] Note: “ / ” in the table means there is no corresponding data.
[0133] Table 2 Electrochemical performance data Note: “ / ” in the table means there is no corresponding data.
[0134] Combined with the above results, when the binder prepared by the present invention is applied to the negative electrode, the internal resistance of the battery is lower and more excellent. Compared with commercially available binders, the negative electrode plate prepared by the binder of the present invention has less swelling in the electrolyte and higher peel strength, and can also enable the battery to have both low internal resistance and high cycle performance. In comparative example 3, no post-crosslinking monomer is added, which makes the swelling degree of the plate greater and the peeling performance worse, affecting the rate performance of the battery, etc. In comparative example 4, the internal crosslinking agent divinylbenzene is added, and crosslinking occurs during the reaction process, the peeling performance deteriorates, and the beneficial effects brought by crosslinking are not significant, which further affects the electrochemical performance of the battery. In comparative example 5, the amount of acrylonitrile added is reduced. During the test, the internal resistance of the battery under low temperature conditions increases, indicating that the total amount of unsaturated nitrile monomer added is regulated to be 65-75wt% of the total mass of the first polymerized monomer and the second polymerized monomer by the present invention, and the content of the unsaturated nitrile monomer in the first polymerized monomer in step (1) is controlled to be not less than 15wt%, so that the polymer can be soluble in water and also have a certain hydrophobic structure; a large amount of unsaturated nitrile monomer is added in step (2), and a polymer component with a unique hydrophilic and hydrophobic structure is obtained together with the intermediate product of step (1), thereby further forming a water dispersion. When the binder is applied to the negative electrode of the battery, the internal resistance of the battery at low temperature can be significantly reduced.
[0135] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.
Claims
1. A method for preparing a water-based binder, characterized in that: The following steps are involved: (1) preparing a protective glue solution; adding a first polymerizable monomer and an initiator to the protective glue solution to carry out a polymerization reaction; the first polymerizable monomer comprises an unsaturated carboxylic acid monomer, an unsaturated nitrile monomer, and an acrylamide monomer; and the content of the unsaturated nitrile monomer in the first polymerizable monomer is not less than 15 wt %; (2) adding a second polymerizable monomer and an initiator to the product of step (1) to carry out a polymerization reaction; the second polymerizable monomer comprises an unsaturated carboxylic acid monomer, an unsaturated nitrile monomer, an acrylamide monomer and a post-crosslinking monomer; Based on the total weight of the first polymerized monomer and the second polymerized monomer, the total content of the unsaturated nitrile monomer in the first polymerized monomer and the second polymerized monomer is 65-75 wt %.
2. The preparation method according to claim 1, characterized in that: The first polymerized monomer accounts for 10-25 wt % of the total weight of the first polymerized monomer and the second polymerized monomer.
3. The preparation method according to claim 1 or 2, characterized in that: The preparation method satisfies at least one of (1)-(2): (1) The mass of the unsaturated carboxylic acid monomer in the first polymerized monomer is not higher than 60 wt % of the total mass of the unsaturated carboxylic acid monomer in the first polymerized monomer and the second polymerized monomer; (2) The total content of the unsaturated carboxylic acid monomer and the acrylamide monomer in the first polymerizable monomer is less than 85 wt %.
4. The preparation method according to any one of claims 1 to 3, characterized in that Based on the total mass of the first polymerized monomer and the second polymerized monomer, the total content of the unsaturated carboxylic acid monomer is 15-30wt%, and / or the total content of the acrylamide monomer is 1-15wt%, and / or the content of the post-crosslinking monomer is not higher than 5wt%.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation method satisfies at least one of (1) to (6): (1) The unsaturated carboxylic acid monomer is at least one of acrylic acid, methacrylic acid, maleic acid and itaconic acid; (2) the unsaturated carboxylic acid monomer is at least one of acrylic acid and methacrylic acid; (3) The unsaturated nitrile monomer is at least one of acrylonitrile, α-haloacrylonitrile, and α-alkylacrylonitrile; (4) The unsaturated nitrile monomer is acrylonitrile; (5) The post-crosslinking monomer is a compound containing an acetoacetyl group; (6) The post-crosslinking monomer is at least one of allyl acetoacetate and acetoacetoxyethyl methacrylate.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The preparation method satisfies at least one of (1)-(2): (1) The protective colloid is at least one of polyvinyl alcohol, polyvinyl pyrrolidone and sodium carboxymethyl cellulose; (2) The amount of the protective glue added is not higher than 1 wt % of the total weight of the first polymerized monomer and the second polymerized monomer.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method satisfies at least one of (1)-(2): (1) The polymerization reaction temperature in step (1) is 30-90° C. and the reaction time is no more than 2 hours; (2) The polymerization reaction temperature in step (2) is 30-90°C and the reaction time is 1.5-5h.
8. A water-based binder obtained by the preparation method according to any one of claims 1 to 7.
9. The aqueous adhesive according to claim 8, characterized in that: The aqueous binder satisfies at least one of (1)-(2): (1) The solid content of the aqueous binder is 5-20%; (2) The viscosity of the aqueous binder is 5000-50000 mPa·S.
10. Use of the aqueous binder prepared by the preparation method according to any one of claims 1 to 7 or the aqueous binder according to any one of claims 8 to 9 as a binder for negative electrode active materials.
Citation Information
Patent Citations
Water-based adhesive, preparation method thereof and application of water-based adhesive in negative electrode of lithium battery
CN116200147A
Binder, positive electrode plate and battery
US20230327121A1